Acute kidney injury in septic patients admitted to emergency clinical room: risk factors and outcome - Medeiros, Pâmela [UNESP]; Nga, Hong Si [UNESP]; Menezes, Precil [UNESP]; Bridi, Ramaiane [UNESP]; Balbi, André Luís [UNESP]; Ponce, Daniela [UNESP] (Japanese Society of Nephrology, 2015)
Acute kidney injury (AKI) is a common source of morbidity in sepsis. We sought to determine risk factors for AKI, by acute kidney injury network (AKIN) criteria, in septic patients admitted in emergency clinical room (ER). Prospective cohort study of 200 patients admitted to the ER of a University Hospital, followed for development of AKI over 5 days. AKI developed in 144/200 (72 %) patients. In multivariable regression analysis, independent risk factors for AKI included age over 65 years (OR 1.28; 95 % CI 1.12-1.89; p = 0.04), mean blood pressure (MBP) lower than 65 mmHg at moment of admission (OR 1.89; 95 % CI 1.43-2.64, p = 0.003) and diabetes mellitus (OR 1.66; 95 % CI 1.30-3.20; p = 0.012). Mortality rate was 51.4 % in AKI patients compared with 26.8 % for those without AKI (p = 0.002). Septic shock (OR = 1.83, 95 % CI 1.23-2.74, p = 0.007), AKIN 3 (OR = 1.64; 95 % CI 1.19-1.89, p = 0.02), APACHE 2 > 20 (OR 1.92, 95 % CI 1.34-2.02, p = 0.009) and need for dialysis (OR = 1.26, 95 % CI 1.13-1.75, p = 0.03) were identified as independent risk factors for death in multivariable regression analysis. AKI severity in septic patients admitted in ER is associated with mortality. Diabetes, age over 65 years, and low MBP are independent risk factors for AKI and deserve further study to prevent AKI and, consequently, decreasing mortality.
Keywords: Acute kidney injury; Emergency clinical room; Epidemiology; Risk factors; Sepsis